Measuring the attitudes of university students towards entrepreneurship (Journal of the College of Basic Education, 2022)
This paper seeks to study the gap that currently exists between students' knowledge and experience with entrepreneurship including the positive impact that this may have on their choice of career, after their graduation, on the one hand and what the years of university education provides for them on the other hand. Therefore, this research aims at firstly measuring the attitude of the students at the college of Basic Education in Salahaddin University towards the introduction of entrepreneurship education and secondly to identify the significance of statistical differences as regards the students trends towards entrepreneurship education gender wise (male: female). The researchers adopted a descriptive methodology as it has been considered to be appropriate for the nature and the aim of the research and the sample of the research which is composed of 196 students that has been selected randomly from among students of the fourth stage of which103 were female and 93 were male students; the percentage of the number of students who participated in the study composed 40.08% of the total number of students at the fourth stage at the college of Basic Education. The researchers adopted a statistical scale that was modified and it consists of four parts and 42 items which coveredstudents' attitudes towards entrepreneurship. The researchers then extracted the psychometric characteristics of the scale, including the apparent honesty and the method of testing and retesting. Likewise, they used several statistical methods to process the data including Satatistical Package for Social Science (SPSS) that is used for logical batched and non-batched Statistical analysis. The result of the study shows that there is a positive trend on behalf of the students at the college of Basic Education in Salahaddin University towards entrepreneurship education as the differences between the figures were statistically significant since the results showed differences between the attitude of the male and female students in this regard. It was noted that the average trends towards entrepreneurship was higher for males than females. That is the attitudes of males towards entrepreneurship were more positive than that of females. In the light of the results, the researchers drew a number of conclusions and recommendations.